Redes de conhecimento: o compartilhamento da informação e do conhecimento em consórcio de exportação do setor moveleiro - Maria Inês Tomaél (2005)
The information sharing and the knowledge construction in networks which permeate the furniture exportation consortium Conex - were studied, focusing on knowledge networks. Knowledge networks are characterized by relations developed by actors who share information and knowledge. The purpose of this research was to study these interactions, typical of knowledge networks that produce the information sharing and the knowledge construction, in the scope of Conex. Due to this, its social network was mapped, the knowledge construction process was identified and the localized character of innovation was distinguished. The methodology used was the Social Networks Analysis (SNA), which consists of a strategy to research the social structure that forms the networks and to present the indicators concerning the guidance of the information flows. In order to be consistent with the research, the quantitative approach peculiar to SNA was united to the qualitative one. The results show that information is an important element that instigates the knowledge construction and may culminate in innovation. The knowledge construction process depends especially on the spontaneous interaction that enables cooperation more appropriately, leading the actors to organize themselves in networks. The consequence of every involvement is characteristic of interactions that start by the information sharing in which, in the scope of Conex, resulted in innovation in the management process and was in synergy with the business processes. The actors who get more information in the network are the most influent ones and the most engaged in the consortium projects. Besides they cooperate in order to strength individual and collective skills. The knowledge network emerges as an important environment for the information sharing and knowledge construction, for strengthening the business processes and projects, and also being indispensable for them as it causes changes in the actors knowledge and actions, transforming the environment.